Environmental geotechnics: challenges and opportunities in the post-Covid-19 world. Issue 3 (2nd October 2020) - Tang, Chao-Sheng; Paleologos, Evan K; Vitone, Claudia; Du, Yan-Jun; Li, Jiang-Shan; Jiang, Ning-Jun; Deng, Yong-Feng; Chu, Jian; Shen, Zhengtao; Koda, Eugeniusz; Dominijanni, Andrea; Fei, Xunchang; et al.
Abstract : The outbreak of the coronavirus disease 2019 (Covid-19) pandemic not only has created a health crisis across the world but is also expected to impact negatively the global economy and societies at a scale that is maybe larger than that of the 2008 financial crisis. Simultaneously, it has inevitably exerted many negative consequences on the geoenvironment on which human beings depend. The current paper articulates the role of environmental geotechnics in elucidating and mitigating the effects of the current pandemic. It is the belief of all authors that the Covid-19 pandemic presents not only significant challenges but also opportunities for the development of the environmental geotechnics field. This discipline should make full use of geoenvironmental researchers' and engineers' professional skills and expertise to look for development opportunities from this crisis, to highlight the irreplaceable position of the discipline in the global fight against pandemics and to contribute to the health and prosperity of communities, to serve humankind better. In order to reach this goal while taking into account the specificity of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and the uncertainty of its environmental effects, it is believed that more emphasis should be placed on the following research directions: pathogen–soil interactions; isolation and remediation technologies for pathogen-contaminated sites; new materials for pathogen-contaminated soil; recycling and safe disposal of medical wastes; quantification of uncertainty in geoenvironmental and epidemiological problems; emerging technologies and adaptation strategies in civil, geotechnical and geoenvironmental infrastructures; pandemic-induced environmental risk management; and modelling of pathogen transport and fate in geoenvironment, among others. Moreover, Covid-19 has made it clear to the environmental geotechnics community the importance of urgent international co-operation and of multidisciplinary research actions that must extend to a broad range of scientific fields, including medical and public health disciplines, in order to meet the complexities posed by the Covid-19 pandemic.